Front Cover: Breastmilk Lipids and Oligosaccharides Influence Branched Short‐Chain Fatty Acid Concentrations in Infants with Excessive Weight Gain. Issue 3 (3rd February 2020) - Pekmez, Ceyda Tugba; Larsson, Melanie Wange; Lind, Mads Vendelbo; Vazquez Manjarrez, Natalia; Yonemitsu, Chloe; Larnkjær, Anni; Bode, Lars; Mølgaard, Christian; Michaelsen, Kim F.; Dragsted, Lars Ove
Abstract : Mol. Nutr. Food Res . 2020, 64, 1900977 DOI: 10.1002/mnfr.201900977 In article 1900977 by Ceyda Tugba Pekmez and co‐workers, infants at five months of age with excessive weight gain receive breast milk with lower human milk oligosaccharide (HMO) diversity, lower levels of α‐linolenic acid, oleic acid, and some phospholipid species. The breast milk phospholipid, free fatty acid, and oligosaccharide levels are associated with fecal branched short‐chain fatty acid concentrations in infants, which may partially explain the excessive weight gain in early life.